Utilização de um ambiente virtual de aprendizagem aliado ao ensino presencial de química analítica - Souza, Talita Galvão (2016)
Based on technological advances, new features have contributed to improvedcommunication and sharingof information and, therefore, have been used as teaching tools. These tools such as computer, videos, internet, blogs and other Virtual Learning Environments (VLE) are called Information and Communications Technologies, or popularly ICTs. In order to discuss the contribution of ICTs in the chemistry teaching,and based on the legislationwhich allowthe use of resources of distance learning as muchas 20% of the workload of graduate courses, this paper proposes the use of VLE in a qualitative analytical chemistry classroom teaching of Federal University of Espírito Santo. Through appeals in AVA, were made available during the course, articles forreading, exercise with answers, video lessons, support materials and forums with the aim of presenting a multiplicity way that scientific knowledge can be shared, as well to facilitate understanding of this knowledge. In addition to these resources, this work included the production of digital animation videos for the purpose of contributing to the process of teaching learning theories that are essential in analytics and chemical equilibrium. With this tool, it intendedto explore the visual aspects in the teaching of chemistry. As a result of the use of technology in education, there was a positive participation ofthe class in the AVA (with an average of 171 hits per student during the course), plus the opinions of students that the use of AVA in classroom teaching can contribute to the teaching and learning process of Qualitative Analytical Chemistry. For 90% of students who shared their opinion on the use of AVA, their experience with the monitoring of the discipline of Qualitative Analytical Chemistry was important because, according to their perceptions, the AVA has contributed to facilitating access to study content, access to teacher, the ability to debate issues and answering questions in the forums and the methodological diversity in education. Similarly, it was found that many students reproduced information shared in the video, the answer contents of questionnaires that were more detailed in videos as well as lessons and other texts. This can be observed in a questionthat was intended to examine the explanation of the theories acid base, for example, as a result, all the students to answer the question and explained 70% of all three theories detailed in the video. At the end of this process, it is clear that ICTs can collaborate with the teaching of chemistry and their potential should be further explored.